ECG Diagnosis: Hyperacute T Waves - Levis, Joel T (Perm J, 2015)
After QT prolongation, hyperacute T waves are the earliest-described electrocardiographic sign of acute ischemia, preceding ST-segment elevation. The principle entity to exclude is hyperkalemia—this T-wave morphology may be confused with the hyperacute T wave of early transmural myocardial infarction.